Study on the Strength Similarity Theory-Based Blasting Compaction Parameters Optimization - Xu Xue-yong; Liu Yuan-yuan; Xiao Xian-bo (E3S Web of Conferences, 2021)
The current blasting compaction faces technical difficulties brought by mud depth increment. The strength similarity theory provides theoretic support for deep mud blasting compaction, offering a large room for blasting parameters optimization. The author applied the strength similarity theory to engineering practice and introduced the deep mud soft foundation blasting compaction, blasting parameters selection, blasting safety and processing effect. According to detection results, the riprap settlement elevation and width can meet design requirements. The riprap bottom interface and bearing layer are well connected. Obvious mud layer is not found in the embankment core. It shows that the application of strength similarity theory achieves the satisfactory effect in the engineering practice.